Ensuring Substantive Justice in Islamic Inheritance Law: The Role of Religious Courts in Protecting Vulnerable Heirs in Indonesia - Nur Azizah; Lestari, Dila Purwa; Agus Maulana Qosim (Berasan: Journal of Islamic Civil Law, 2025)
This study examines how substantive justice is ensured in the application of Islamic inheritance law through the role of religious courts in protecting vulnerable heirs. The research aims to analyze judicial reasoning in resolving inheritance disputes and to assess how religious courts balance normative faraidh provisions with the need for equitable legal protection. Employing doctrinal legal research with a case law approach, this study analyzes Decision Number 164/Pdt.G/2025/PA.Amt of the Amuntai Religious Court, supported by statutory analysis of the Compilation of Islamic Law and relevant Qur’anic provisions. The findings indicate that the court did not merely apply inheritance formulas textually, but exercised judicial discretion to uphold substantive justice, particularly by recognizing the legal status of vulnerable heirs, appointing guardianship arrangements, and imposing provisional seizure to prevent the misuse of inherited assets. This approach demonstrates the court’s active role in safeguarding the rights and interests of heirs who are structurally disadvantaged within family disputes. The study concludes that religious courts function not only as normative law enforcers, but also as key institutions in bridging the gap between formal Islamic inheritance rules and substantive justice. This contributes to broader discussions on the dynamic interpretation of Islamic family law in contemporary legal practice.